The risk premium of gold - Duc Binh Benno Nguyen; Marcel Prokopczuk; Chardin Wese Simen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper examines the properties of the gold risk premium. We estimate a parsimonious model for the gold risk premium and uncover important time variations in the dynamics of the risk premium. We also estimate risk premia of the stock and bond markets, and investigate the role of gold as a hedge and safe haven asset from an ex-ante point of view. The results show that gold is not expected to serve as hedge and safe haven for the bond and stock markets, but it is so realized ex-post. Further, we find that gold is neither expected to be an inflation hedge nor is it realized.
Keywords: G01; G10; G11; Q02; 330; Jump Risk; Tail Risk; Safe Haven; Hedge; Gold